Komunikasi Dalam Pembelajaran Di Masa Pandemi - Rumra, Fatmawati (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
This study aims to describe the implementation of communication in the learning process between teachers and students during the SMA Negeri 21 Maluku Tengah pandemic, covering both online and offline learning. This qualitative study explores all forms of actions and phenomena carried out by the subjects being studied in the implementation of online and offline learning. Data collection techniques in this research involved observations and interviews with several informants engaged in the learning process. The results of this study indicate that the implementation of online and offline learning at SMA Negeri 21 Maluku Tengah for grade 2 has been conducted quite well. Students and teachers have the basic facilities needed, reflecting their readiness for online learning. In the implementation of online learning, teachers have done good planning and have carried out the learning process using appropriate learning media, strategies, methods, and approaches tailored to the needs of the students. Additionally, in face-to-face learning, teachers can interact directly with students, explain the material clearly, and communicate without parental intermediaries. Ensures that communication between students and teachers in the educational process is effectively conveyed. Students are encouraged to be more active and motivated in learning.